Surgical complications in pediatric patients with hydrocephalus in Guillermo Almenara-Irigoyen Nacional Hospital - Erwinovna Mogrovejo, Estela (2011)
Objective: To determine the main surgical complications in pediatric patients with hydrocephalus in Guillermo Almenara Irigoyen National Hospital. Material and method: A descriptive case series reviewed the charts of pediatric patients with hydrocephalus who underwent a ventriculo-peritoneal shunt procedure. These patients were between 0 and 14 years old when they had their first surgery. Data was collected in a standardized chart. Statistical significance was established in p<0.05. Results: Approximately one third of patients (35.5%) developed complications. Fifty- four percent had early complications and 45% developed late complications. Causes for complications were: system malfunction, infection and subdural hematoma caused by overdrainage of VP shunts in 54.5%, 27.3% and 18.2%, respectively. Of all patients who developed complications, 54.5% had acquired and 45.5% had congenital hydrocephalus; 72.7% underwent emergency surgery and 27.3% underwent elective surgery. There was a statistically significant association between the origin of hydrocephalus and the development of complications, X2 = 5.387 (p = 0.02).   Conclusions: The frequency of complications after surgical therapy for hydrocephalus was 35.5%. The main cause was system malfunction. These results show that acquired hydrocephalus has a greater likelihood for developing post surgical complications compared to congenital hydrocephalus.